2022
DOI: 10.3390/universe8030165
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutativity, Sáez–Ballester Theory and Kinetic Inflation

Abstract: This paper presents a noncommutative (NC) version of an extended Sáez–Ballester (SB) theory. Concretely, considering the spatially flat Friedmann–Lemaître–Robertson–Walker (FLRW) metric, we propose an appropriate dynamical deformation between the conjugate momenta and, applying the Hamiltonian formalism, obtain deformed equations of motion. In our model, the NC parameter appears linearly in the deformed Poisson bracket and the equations of the NC SB cosmology. When it goes to zero, we get the corresponding com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…into the WDW Equation (12). Straightforward differentiation plus condition (14) (which is equivalent to WKB) (The semi-classical approximation and also the WKB wave function are important concepts in the context of quantum cosmology.…”
Section: Wheeler-dewitt Equation In Slow Roll Regimementioning
confidence: 99%
See 2 more Smart Citations
“…into the WDW Equation (12). Straightforward differentiation plus condition (14) (which is equivalent to WKB) (The semi-classical approximation and also the WKB wave function are important concepts in the context of quantum cosmology.…”
Section: Wheeler-dewitt Equation In Slow Roll Regimementioning
confidence: 99%
“…Note that in a particular case where α = 2, Equation ( 27) reduces to its standard counterpart (12). To obtain the semi-classical solution of this fractional WDW equation, we use the alternative equivalent representation of the Riesz fractional derivative (or fractional Laplacian) [60], given by…”
Section: Fractional Quantum Cosmology For a Slow Roll Regimementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the latter, the SB theory includes the action of ordinary matter that is not coupled to the SB scalar field. Various cosmological models have been established in the context of the SB theory to study open problems in both the classical and quantum regimes [49][50][51][52][53][54]. Applying the similar reduction procedure used to construct the MBDT, without assuming the presence of the higher dimensional matter fields and imposing the cylindricity condition on the extra coordinate, it has been shown that the SB field equations associated to the bulk split into four sets of effective field equations on any hypersurface orthogonal to the extra dimension [9].…”
Section: Introductionmentioning
confidence: 99%
“…Adler-Deser-Misner (ADM); see[50] for more details 5. In this work, we consider a framework in which the scalar field is minimally coupled to gravity, see also[51,52,53]. Instead, one can choose other interesting gravitational models where φ is non-minimally coupled, see for instance,[54,55,56,57,58].…”
mentioning
confidence: 99%